2002
DOI: 10.1152/ajprenal.00273.2001
|View full text |Cite
|
Sign up to set email alerts
|

Polaris, a protein disrupted inorpkmutant mice, is required for assembly of renal cilium

Abstract: Cilia are organelles that play diverse roles, from fluid movement to sensory reception. Polaris, a protein associated with cystic kidney disease in Tg737°rpk mice, functions in a ciliogenic pathway. Here, we explore the role of polaris in primary cilia on Madin-Darby canine kidney cells. The results indicate that polaris localization and solubility change dramatically during cilia formation. These changes correlate with the formation of basal bodies and large protein rafts at the apical surface of the epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
197
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(202 citation statements)
references
References 57 publications
5
197
0
Order By: Relevance
“…34,35 We recently reported that downregulation of Pkhd1 significantly decreases ciliary formation in cultured Pkhd1-silenced IMCD cells, suggesting that lack of FPC might disrupt ciliogenesis in renal epithelial cells. This result is consistent with studies in which transient small interference RNA-mediated inhibition of Pkhd1 in cholangiocytes resulted in shortening and decreased formation of cilia, 29 but spatial and environmental differences between in vivo tissues and in vitro cell culture may lead to different results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 We recently reported that downregulation of Pkhd1 significantly decreases ciliary formation in cultured Pkhd1-silenced IMCD cells, suggesting that lack of FPC might disrupt ciliogenesis in renal epithelial cells. This result is consistent with studies in which transient small interference RNA-mediated inhibition of Pkhd1 in cholangiocytes resulted in shortening and decreased formation of cilia, 29 but spatial and environmental differences between in vivo tissues and in vitro cell culture may lead to different results.…”
Section: Discussionmentioning
confidence: 99%
“…FPC was demonstrated to localize to the primary cilium and/or basal bodies of renal tubular epithelia, [27][28][29][30][31] and malformation of the cilia was shown to induce cyst formation in the kidneys 34,35 ; therefore, we began to determine whether the lack of FPC also disrupts ciliogenesis in Pkhd1-deficient mice. We used IF with an anti-acetylated ␣-tubulin antibody to examine the number and morphology of renal primary cilia in 6-moold littermates.…”
Section: Lack Of Fpc Exhibits Aberrant Ciliogenesis In the Renal Epitmentioning
confidence: 99%
“…In tetrahymena pyriformis, it has been shown that colchicine does not disrupt existing ciliary axonemes 30 and we found previously that vinblastine, a drug with a similar mechanism of action, left the ciliary axoneme of human embryonic kidney cells (HEK293T) intact 31 . At the same time, nocodazole in moderate to high concentrations has been shown to disrupt the ciliary axoneme along with the MT network 32,33 . In line with these observations, nocodazole dissolved the MT skeleton including the ciliary axoneme of the MIN6m9 b-cell line, whereas colchicine did not disassemble the ciliary axoneme ( We cannot exclude an effect of colchicine on ciliogenesis, although a parsimonious explanation might be the improved visibility of ciliary axonemes because of the absence of other acetylated MT structures that otherwise mask the axonemes.…”
Section: Disruption Of Basal Body Integrity Impairs Insulin Secretionmentioning
confidence: 99%
“…69,60,70 Although nephrocystin 3 and nephrocystin 4 have not been localized to cilia, nephrocystin 4 forms a complex with nephrocystin, suggesting that they may be colocalized in cilia. 63 Disruption of several additional genes in mouse also leads to PKD, and the protein products of at least two, cystin 65,71 and polaris/Tg737, 65,[72][73][74] are localized to cilia.…”
Section: Polycystic Kidney Diseasementioning
confidence: 99%